The use of Nanotrap particles for biodefense and emerging infectious disease diagnostics. Issue 2 (20th March 2014) - Shafagati, Nazly; Patanarut, Alexis; Luchini, Alessandra; Lundberg, Lindsay; Bailey, Charles; Petricoin, Emanuel; Liotta, Lance; Narayanan, Aarthi; Lepene, Benjamin; Kehn‐Hall, Kylene
Abstract Detection of early infectious disease may be challenging due to the low copy number of organisms present. To overcome this limitation and rapidly measure low concentrations of the pathogen, we developed a novel technology: Nanotrap particles, which are designed to capture, concentrate, and protect biomarkers from complex biofluids. Nanotrap particles are thermoresponsive hydrogels that are capable of antigen capture through the coupling of affinity baits to the particles. Here, we describe recent findings demonstrating that Nanotrap particles are able to capture live infectious virus, viral RNA, and viral proteins. Capture is possible even in complex mixtures such as serum and allows the concentration and protection of these analytes, providing increased performance of downstream assays. The Nanotrap particles are a versatile sample preparation technology that has far reaching implications for biomarker discovery and diagnostic assays.